Development of an E-Book Based on Local Wisdom of Fish Ponds in Gresik to Train Scientific Reasoning Skills - Rosyidah, Fitrotin; Susantini, Endang; Puspitawati, Rinie; Nursanti, Arie (Universitas Negeri Surabaya, 2023)
Objective: Scientific reasoning is one of the most essential skills in learning biology and can be trained by integrating local wisdom. The lack of learning media that facilitates student learning causes low students' scientific reasoning skills. The development of learning media that integrates local wisdom is needed to train students' scientific reasoning. Method: The e-Book development procedure uses the ASSURE model which consists of six stages namely (1) analyze learner characteristics, (2) state objectives, (3) select, modify or design media, (4) utilize media, (5) requires learner responses, dan (6) evaluate. Data collection was collected by validation, observation, tests, and student response questionnaires. The One-Group Pretest-Posttest Design was implemented at Muhammadiyah 10 High School Surabaya for the 2022/2023 school year. Results: The results showed that (1) the developed e-book was valid with an average validity value of 93%, (2) learning implementation was 92.5% at the first meeting, and 81% at the second meeting with the high category, (3 ) student learning outcomes in the scientific reasoning indicator increased to 88% in probabilistic reasoning, 82% in theoretical reasoning, 80% in correlation reasoning and 79% in proportional reasoning, as well as the n-Gain calculation results which with high criteria and (4) positive student responses to the use of e-books. So that the developed e-book is feasible to use in terms of local wisdom potential, e-book validity, practicality, and e-book effectiveness. Novelty: The development of an e-book on ecosystem material with the integration of local wisdom from fish ponds to train scientific reasoning skills has never been done before.